2023
DOI: 10.1111/jep.13817
|View full text |Cite
|
Sign up to set email alerts
|

The COVID‐19 impact and characterization on substance use‐related emergency department visits for adolescents and young adults in Canada: Practical implications

Abstract: Rationale Coronavirus (COVID‐19)‐related stressors precipitated the mental health crisis and increased substance use in Canada and worldwide. As the pandemic continues to evolve, monitoring and updating substance use‐related ED visit trends is essential to ensure the stability and quality of ED services under the prolonged pandemic timeline. Aims and Objectives This study examined the trends and characterization of substance use‐related ED visits during the pandemic among adolescents and young adults (aged 13–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…A Québec study found increases in hospitalizations post-legalization among boys aged 10–14 years, with 70% of substance-related hospitalizations after legalization involving cannabis, compared with 39.3% pre-legalization [ 87 ]. Kim et al [ 81 ] studied ED visits in Ontario and found that cannabis-related visits increased in 2020 compared to 2019 among young adults 18–25 years more than among youth 10–17 years. Additionally, young adults with cannabis-related ED visits had triage to end times longer than six hours with higher rates of emergent or life threatening triage levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Québec study found increases in hospitalizations post-legalization among boys aged 10–14 years, with 70% of substance-related hospitalizations after legalization involving cannabis, compared with 39.3% pre-legalization [ 87 ]. Kim et al [ 81 ] studied ED visits in Ontario and found that cannabis-related visits increased in 2020 compared to 2019 among young adults 18–25 years more than among youth 10–17 years. Additionally, young adults with cannabis-related ED visits had triage to end times longer than six hours with higher rates of emergent or life threatening triage levels.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies included data from both Canada and the United States [74,75] and one included data from Canada, the United States, and England [76]. The remaining studies gathered data from a single province, with eleven studies in Ontario [77][78][79][80][81][82][83][84][85][86]95], four in Québec [4,15,20,87], two in Manitoba [88,89], two in British Columbia [90,91], and one each in Saskatchewan [92], Alberta [93], and Newfoundland and Labrador [94].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the absolute number of unintentional deaths due to opioid toxicity and the associated YLL among those younger than 40 years far exceeded those attributable to COVID-19 in both 2020 and 2021, indicating the distinct impact of drug toxicity-related deaths among younger individuals. This aligns with previous observations of accelerating substance-related harm among adolescents 10 and warrants further attention and expansion of harm reduction and treatment programs tailored to this demographic population.…”
Section: Discussionmentioning
confidence: 99%
“…Across Canada, mental health and substance use service utilization during the pandemic has mostly suggested a decline in emergency department and hospital visits ( 18 , 19 ) with hospitalization rates returning to pre-pandemic levels by March 2021 ( 20 ). Evidence from Ontario, Canada using population-level administrative data found psychiatric-related hospital admissions did not return to pre-restriction rates ( 21 ) and while overall volumes may have decreased, monthly increases were observed for specific mental disorders post pandemic ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%